Case-control study of lung cancer among sugar cane farmers in India. Issue 8 (1st August 1999) - Amre, D K; Infante-Rivard, C; Dufresne, A; Durgawale, P M; Ernst, P
Abstract : OBJECTIVES: To investigate the risk of lung cancer among sugar cane farmers and sugar mill workers. METHODS: A case-control study was conducted based in six hospitals in the predominantly sugar cane farming districts of the province of Maharashtra in India. Newly diagnosed, histologically confirmed cases were identified from these hospitals between May 1996 and April 1998. Other cancers were chosen as controls and matched to cases by age, sex, district of residence, and timing of diagnosis. RESULTS: Adjusting for confounders, an increased risk of lung cancer was found for workers ever employed on a sugar cane farm (odds ratio (OR) 1.92, 95% confidence interval (95% CI) 1.08 to 3.40). Increased risks were found for work involving preparation of the farm (OR 1.81, 95% CI 0.99 to 3.27) and burning of the farm after harvesting (OR 1.82, 95% CI 0.99 to 3.34). Non-significant increases in risks were found for harvesting the crop (OR 1.41, 95% CI 0.70 to 2.90) and processing the cane in the mills (OR 1.70, 95% CI 0.20 to 12.60). CONCLUSIONS: Exposure to fibres of biogenic amorphous silica (BAS) formed from silica absorbed from the soil and deposited in the leaves of the sugar cane crop or crystalline silica formed as a result of conversion of BAS to cristobalite at high temperatures may account for the increased risks of lung cancer among sugar cane farmers.